IMPLEMENTASI PERATURAN BUPATI PONOROGO NOMOR 23 TAHUN 2019 TENTANG MASTERPLAN DAN ROADMAP TEKNOLOGI INFORMASI DAN KOMUNIKASI KABUPATEN PONOROGO TAHUN 2019 - 2023 - Sulistyono, Joni (JI@P, 2021)
The Master Plan and Information and Communication Technology Roadmap policies in Ponorogo Regency have been implemented. However, there are still deficiencies in its implementation. These deficiencies include the results of communication that have not been implemented properly, resources consisting of strategic plans, main duties and authority of cooperation do not provide support for policy implementation, the disposition of outstanding policy implementers has not been followed by a good reward system and the existing organizational structure has not implemented the program. and activities that are relevant to the targets set.